HARGA POKOK PRODUKSI, NILAI TAMBAH, DAN PROSPEK PENGEMBANGAN AGROINDUSTRI MARNING DI KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN - Dwi Rizky Agustina; R Hanung Ismono; Adia Nugraha (Lampung University, 2015)
The research aimed to analyze the cost of production, the proportion of the added value, and identification of agroindustry development prospects of marning if cultivated more. This study was conducted on purpose in the village of Karang Anyar Gedong Tataan Subdistrict of Pesawaran Regency. This study uses census method in determining the sample, methods of data analysis using variable costing method, a full costing method, the method hayami, and identification of internal factors and external factors. Respondents totaled 27 marning processors. The results showed that the cost of production agroindustry marning with variable costing method is Rp9.634,76 and the method of full costing Rp9.809,55. The cost of production is amount of cost that used in producing perkilogram of marning. The added value of the agroindustry of marning was Rp3,715.88 per kilogram. Percentage of labor remuneration to the added value was equal to 53.15 percent and the percentage of owners of agroindustry profits amounted to 46.85 percent of the value added. Marning agroindustry has good prospects when views from the identification of the availability of raw materials, labor availability, supply of marning, competitors, regional product marketing, public support, and the support of government. Key words: added value, agroindustry, development prospects, marning, the cost of production